2018
DOI: 10.26432/1809-3019.2018.63.2.77
|View full text |Cite
|
Sign up to set email alerts
|

Conhecimento de enfermeiros de Unidades de Terapia Intensiva acerca da notificação de eventos adversos

Abstract: Objetivo: Verificar o conhecimento de enfermeiros de Unidade de Terapia Intensiva (UTI) adulto sobre a ocorrência e notificação de eventos adversos (EA). Método: Pesquisa de campo, exploratória, descritiva, de natureza quantitativa, realizada entre treze (13) enfermeiros intensivistas. Os dados foram coletados por meio de um questionário semiestruturado, aplicado em duas UTIs de um Hospital geral e público da cidade de São Paulo, após aprovação pelo Comitê de Ética em Pesquisa da instituição (sob número 797188… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…7,9 It is observed that this study contributes to the theoretical development of health professionals regarding vasoactive drugs in the context of intensive therapy, to correlate the results and other scientific works, evidencing the need to enhance the professionals' learning about the proposed theme and, thus, to develop a service free of errors and damages. 20 The main difficulties encountered during the study were a reduced sample of eight participants and the limitation of research related to the topic, but the issues addressed for the analysis included the studied population and demonstrated support for other larger, relevant to the scope of critical patient care.…”
Section: Resultsmentioning
confidence: 99%
“…7,9 It is observed that this study contributes to the theoretical development of health professionals regarding vasoactive drugs in the context of intensive therapy, to correlate the results and other scientific works, evidencing the need to enhance the professionals' learning about the proposed theme and, thus, to develop a service free of errors and damages. 20 The main difficulties encountered during the study were a reduced sample of eight participants and the limitation of research related to the topic, but the issues addressed for the analysis included the studied population and demonstrated support for other larger, relevant to the scope of critical patient care.…”
Section: Resultsmentioning
confidence: 99%